PERAN ADVOKAT DALAM PEMBERIAN BANTUAN HUKUM KEPADA PENCARI KEADILAN PERKARA PERDATA - fatich nurhadi; Hasriyani (Yuriska: Jurnal Ilmiah Hukum, 2024)
Background: This research is entitled "The Role of Advocates in Providing Legal Aid to Justice Seekers in Civil Cases". Research Metodes: This research method is normative law, which prioritizes collecting initial data from library materials relating to the problem researched by the author. Field research was conducted to support and complement this data. Findings: Based on several facts that occur in Legal Aid Institutions/Legal Aid Organizations or abbreviated as LBH/OBH, there are many goals of Legal Aid that have not been realized in Providing to the Community is carried out affordably and for free so that all Indonesian Citizens can access justice easily and without having to pay comprehensively cannot be done however, because of him; all this because there are many costs that need to be handled in Indonesia in each data case. Conclusion: This is the concern for legal aid providers to raise the masses.